Enhancing tenth graders’ reading comprehension through the fix-up strategy in Indonesian classrooms: a quasi-experimental study - Mirella Angelina; Annisa Astrid; Husnaini (Erudita: Journal of English Language Teaching, 2026)
This study examines the effectiveness of the Fix-Up Strategy in enhancing tenth graders’ reading comprehension in Indonesian EFL classrooms. Although metacognitive reading strategies have been widely studied, empirical evidence on the Fix-Up Strategy in Indonesian secondary school contexts remains limited. This study investigates (1) the improvement in students’ reading comprehension after instruction using the Fix-Up Strategy and (2) the difference in reading comprehension achievement between students taught using the Fix-Up Strategy and those receiving conventional instruction. A quantitative quasi-experimental method with a matching-only pretest–posttest control group design was employed. Sixty tenth-grade students in an Indonesian private Islamic senior high school participated in the study. Data were collected using a 40-item multiple-choice reading comprehension test and analyzed using descriptive statistics, normality and homogeneity tests, paired-samples t-tests, and independent-samples t-tests. The results revealed a significant improvement in the experimental group's reading comprehension achievement (p < .001, Cohen’s d = 3.43, indicating a very large effect) and a significant difference in posttest scores between the experimental and control groups (p < .001, Cohen’s d = 1.10, indicating a large effect). These results indicate that the Fix-Up Strategy effectively enhances students’ reading comprehension and supports the integration of metacognitive reading strategies into English instruction in Indonesian secondary schools.